ANALISIS PENGARUH KEADAAN EKONOMI MAKRO TERHADAP INVESTASI ASURANSI JIWA SYARIAH DI INDONESIA TAHUN 2010 – 2019 - Khalish Khairina (IAIN Langsa, 2020)
This study aims to analyze the effect of Inflation, Exchange Rate, BI Interest Rate, Indonesia Composite Index on Sharia Insurance Life in Indonesia.  Data used is time series data for 10 years (2010-2019) and analyzed by using Eviews 10. This research using quantitative descriptive method, and to analyze the effect of independent variables toward dependent variables using Ordinary Least Square technique. The result of t ? test shows Inflation, Exchange Rate, Indonesia Composite Index have significant influence to Sharia Life Insurance Investment in Indonesia that t ?test < 0,05 and Interest Rate doesn?t influence to Sharia Life Insurance Investment in Indonesia with t ? test > 0,05. However, independent variables has a significant influence with the result of F test 0,000002 < 0,05 and Adjusted R-Squared test shows that 99,41 %  of Sharia Life Insurance Investment in Indonesia is influenced by independent variables in this research